Nutritional composition and optimization of extraction conditions of cocoa pod husk using response surface methodology - Azhar, Nurulain Hasya; Zaidan, Uswatun Hasanah; Shamsi, Suhaili; Abd Gani, Siti Salwa; Md Yusof, Arief Huzaimi (Persatuan Biologi Gunaan Malaysia,Malaysian Society of Applied Biology, 2023)
Cocoa pod husks (CPH) are usually disposed of from the farm, and this can lead to environmental problems, such as being a breeding ground for the cocoa pod borer. This study aimed to determine the nutritional composition and concentration of ultra-trace elements (As, Cd, Pb & Hg) in CPH. The optimization of the extraction conditions of CPH in response to the ferric-reducing antioxidant power (FRAP) by using response surface methodology (RSM) was also conducted. The findings show that the total carbohydrate and crude fibre content of CPH are high (35.75% & 35.47%, respectively) while having low levels of moisture, ash, crude protein, and fat (11.86%. 8.60%, 7.46% & 0.86, respectively). In addition, the results demonstrate that CPH has a low content of toxic metals As, Cd, Pb, and Hg (0.0046 mg/kg, 0.0028 mg/kg, 0.0011 mg/kg & 0.00003 mg/kg respectively) which is considered as a safe range. The optimized extraction conditions were a solvent concentration of 93.64%, a temperature of 38.18°C, and a time of 73.64 min. The actual value of the flavonoid content of CPH obtained was 1038.94 µmoL Fe2+/L, which is acceptable compared to the predicted value of 1039.40 µmoL Fe2+/L. The discovery from this research represents a significant contribution towards finding cocoa pod husk from a plentiful, affordable, and feasible source, which could potentially be used in various fields such as pharmaceutical, medical, and nutraceuticals.